Method of creating a radar network for hydrometeorological monitoring of the atmosphere - Перелыгин, Б.В. (Radiotekhnika, 2019)
It is proposed to place radars with a range of up to 100 kilometers in such a way that their totality forms a hexagonal grid on the ground, while the distance between adjacent radars should be equal to the range of radars, when creating a radar network for hydrometeorological monitoring of the atmosphere. Due to such a network construction, the capabilities of the radar method of monitoring the atmosphere are approaching the potentially possible and thus the quality of monitoring is improved.